Impact of the train heights on the aerodynamic behaviour of a high-speed train - Kaiwen Wang; Xiaohui Xiong; Chihyung Wen; Xiaobai Li; Guang Chen; Zhengwei Chen; Mingzan Tang (Engineering Applications of Computational Fluid Mechanics, 2023)
The impact of train heights on train aerodynamic performance is studied by using an improved delayed detached-eddy simulation (IDDES) method. The correctness of the numerical method has been verified by the existing wind tunnel and moving model experiments data. The aerodynamic drag, lift, slipstream, and wake flow are compared for three train heights. The results presented that the drag and lift increased by 6.2% and 23.8% respectively, with an increase in train height from 3.89 m to 4.19 m. Compared with the 3.89 m case, the maximum time-averaged slipstream at the platform location for 4.04 and 4.19 m cases are increased by 2.0% and 4.3% respectively. Meanwhile, the wake topology for three cases is described and analyzed quantitatively. The downwash angle of the wake longitudinal flow is increased with the increasing train height, resulting in the mixing of the downwash flow and the ground flow in advance. The wake in the higher trains tends to develop outward and downward. Besides, the higher trains will also bring greater transient aerodynamic loads to the equipment above the train. It’s recommended to shorten the maintenance period of the electrical equipment above the higher trains to ensure the devices’ safety.Abbreviations: CFL: Courant–Friedrichs-Lewy; COT: Center of the track; FDR: Flow development region; FFT: Fast Fourier transform; GF: Ground-fixed reference system; ICE3: Intercity Express 3; IDDES: Improved delayed detached-eddy simulation; LES: Large-eddy simulation; LV: Longitudinal vortex; MME: Moving model experiments; NBL: Negative bifurcation line; PBL: Positive bifurcation line; PSD: Power spectral density; RANS: Reynolds averaged Navier – Stokes; SF: Stable focus; SP: Saddle point; STBR: Single-track ballast and rails; SV: Spanwise vortex; TF: Train-fixed reference system; TOR: Top of the track; TSI: Technical specification for interoperability; UN: Unstable node; WPR: Wake propagation region